Effectiveness of information processing strategy training on academic task performance in children with learning disabilities: A pilot study - Sutinun Juntorn (2018)
© 2017 Sutinun Juntorn et al. Learning disabilities (LD) can be associated with problems in the four stages of information processing used in learning: input, throughput, output, and feedback. These problems affect the child’s ability to learn and perform activities in daily life, especially during academic activities. This study is a pilot study aimed at investigating the effectiveness of information processing strategy training using a combination of two approaches that address the ability to apply processing strategies during academic activities in children with LD. The two approaches are the Perceive, Recall, Plan, and Perform(PRPP) System of Intervention, which is a strategy training intervention, and the Four-Quadrant Model (4QM) of Facilitated Learning approach, which is a systematic facilitator technique. Twenty children with LD were assigned to two groups: the experimental group (n = 10) and the control group (n = 10). Children in the experimental group received the intervention twice a week for 6 consecutive weeks. Each treatment session took approximately 50 minutes. Children in the control group received traditional intervention twice a week for 6 consecutive weeks. The results indicated that the combination of the PRPP System of Intervention and the 4QM may improve the participants’ ability to apply information processing strategies during academic activities.